Stoikisme dalam Mengatasi Perilaku Agresif Siswa - Victor Novianto; Feryda Indriyanti Putri (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to determine how stoicism overcome the aggressive behavior of students of SMA Negeri 1 Bandongan and how the Harmony of stoicism with the teachings of Islam in overcoming the aggressive behavior of students of SMA Negeri 1 Bandongan. This research uses descriptive-analysis method with qualitative approach and literature review as the main reference source. The results and discussion in this study found there are four (4) main ideas of Stoicism whose values in life are very close to the reality of life and can be used to overcome aggressive behavior in students at SMA Negeri 1 Bandongan, namely (1) dichotomy of control, (2) premeditatio malorum, (3) amor fati, and (4) memento mori. In addition, based on searches in various literatures, several stoicism philosophical teachings were obtained that have similar concepts to Islamic religious teachings, especially those related to the term happiness of life, namely amor fati and gratitude, qona'ah and a sense of sufficiency. patience and emotional control, sunnatullah and live in nature as well as apatheia and asceticism.